2x-5y-6z=

Simple and best practice solution for 2x-5y-6z= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-5y-6z= equation:


Simplifying
2x + -5y + -6z = 0

Solving
2x + -5y + -6z = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5y' to each side of the equation.
2x + -5y + 5y + -6z = 0 + 5y

Combine like terms: -5y + 5y = 0
2x + 0 + -6z = 0 + 5y
2x + -6z = 0 + 5y
Remove the zero:
2x + -6z = 5y

Add '6z' to each side of the equation.
2x + -6z + 6z = 5y + 6z

Combine like terms: -6z + 6z = 0
2x + 0 = 5y + 6z
2x = 5y + 6z

Divide each side by '2'.
x = 2.5y + 3z

Simplifying
x = 2.5y + 3z

See similar equations:

| 4.4x-7.8x=21.08 | | x+x+1+x+2+x=192 | | (.25)4y=5(.25) | | 2x+14=-11-3x | | 3x+2y=12y | | 15+g=27 | | 7y-11-10y+3=7 | | -1+49x=21x+43 | | 1/2*2+13=9 | | 9.2(+6.4)=132.48 | | t+13=18 | | -5q+9=-4q | | y=6*x | | x^2+(y^2)+z^2=z | | 5+2(x-3)=8+7 | | q-6=8 | | 18-5x=12-7x | | 2sin(x)tan(x)=3 | | 4x-3y-12z= | | 28y-1=5 | | 5-4y=8 | | 4x^3+4x-4=0 | | 7y-11-10y+3= | | 25+0.05n=7+0.11n | | 4x^3+4x=4 | | 647=6x-99.4 | | 5x-7=4x+36 | | 12g-(-7)=31 | | 5x+32=8x-13 | | m-16=6 | | 5=-x+5 | | -1.5f+24=10.50 |

Equations solver categories